The Effect of Price Fairness, Brand Image, and Perceived Value on Satisfaction and Word of Mouth of Go-Jek Customers - Innocentius Bernarto; Zoel Hutabarat; Agus Purwanto (International Journal of Artificial Intelligence Research, 2022)
The purpose of this study was to analyze the relationship between price fairness, brand image, and perceived value on Satisfaction and Word of Mouth of Go-Jek Customers. The survey method was applied in this study. Methods of data collection by using a questionnaire (google form). The target population in this study were all Go-jek customers in JABODETABEK within October 2021. The sampling technique was done by convenience sampling. In this study, the number of samples was 184 respondents. Data analysis with partial least square-structural equation modeling (PLS-SEM) approach with the help of SmartPls 3.0 program. Based on the data analysis, it was found that price fairness has a positive effect on satisfaction, brand image has a positive effect on satisfaction, perceived value has a positiveÂ  effect on satisfaction and satisfaction has a positive effect on Word of Mouth. The perceived value variable gives the greatest contribution to satisfaction